2021
DOI: 10.1038/s41525-021-00183-y
|View full text |Cite
|
Sign up to set email alerts
|

A cryptic splice-altering KCNQ1 variant in trans with R259L leading to Jervell and Lange-Nielsen syndrome

Abstract: Here we report an infant with clinical findings suggestive of Jervell and Lange-Nielsen syndrome (JLNS), including a prolonged QT interval (LQTS) and chronic bilateral sensorineural deafness. NGS analysis revealed one known heterozygous pathogenic missense variant, KCNQ1 p.R259L, previously associated with LQTS but insufficient to explain the cardioauditory disorder. In a screening of proximal intronic regions, we found a heterozygous variant, KCNQ1 c.1686−9 T > C, absent from controls and previously undesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…RNA analysis using either patient blood cells or immortalized lymphoblastoid cells represents an alternative option, providing that the gene of interest is normally expressed in these cells (Wai et al, 2020). In case of the non-feasibility of both approaches, a cell culture-based minigene splicing assay has often been devised (for some most recent examples, see Damasio et al, 2021;Hao et al, 2021;Kim et al, 2021;Kortum et al, 2021;Le Tertre et al, 2021;Morbidoni et al, 2021;Qian et al, 2021;Saint-Martin et al, 2021;Torrado et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…RNA analysis using either patient blood cells or immortalized lymphoblastoid cells represents an alternative option, providing that the gene of interest is normally expressed in these cells (Wai et al, 2020). In case of the non-feasibility of both approaches, a cell culture-based minigene splicing assay has often been devised (for some most recent examples, see Damasio et al, 2021;Hao et al, 2021;Kim et al, 2021;Kortum et al, 2021;Le Tertre et al, 2021;Morbidoni et al, 2021;Qian et al, 2021;Saint-Martin et al, 2021;Torrado et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This result may explain QT interval prolongation observed on the ECG scan. There is not much literature about exon 16 deletion but some authors have reported that young patients with deletions in exon 15 and 16 showed prolonged QTc 13,14 . Importantly, a small domain between residues 589 and 620 (i. e. within exon 16) in the KCNQ1 c-terminus may function as an assembly domain for KCNQ1 subunits 15 .…”
Section: Discussionmentioning
confidence: 99%
“…29,30 The genetic mutations of KCNQ1 gene have been reported to be related to type 2 diabetes, 31 cardiovascular diseases 32 and deafness. 33,34 Thus far, only a GWAS research of Han Chinese found a correlation of KCNQ1 variants with gout while not hyperuricemia, 14 which mechanisms supposed be responsible of immune regulation. The amplification of inflammation of KCNQ1 blocker intervention in our gout mouse model was consistent with the hypothesis that KCNQ1 mediates gouty inflammation.…”
Section: Discussionmentioning
confidence: 99%